PENGARAUH KEKAYAAN SUMBERDAYA ALAM TERHADAP PERKEMBANGAN EKONOMI WILAYAH - Nandang Najmulmunir (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2003)
Natural resources policy have enhanced the development of primary sector which produced the primary out put. So that primary output will be taken by region where the natural resources located. But in the other side the secondary output or tertiary output did not depend on with the location of natural endowment. The deference of speed of spreading of each out put has brought the different in the development of kabupaten region.